2008
DOI: 10.1111/j.1365-2702.2007.02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Heights of occupied patient beds: a possible risk factor for inpatient falls

Abstract: A higher patient/nurse ratio at weekends than on weekdays may result in fewer bedside nursing hours and nurses being less conscientious about keeping beds in the low position after treatments. In an effort to prevent high-fall-risk patients from falling, nurses may have consciously or unconsciously kept their beds in higher positions. Relevance to clinical practice. If the patient bed can be manually or automatically adjusted, nurses must lower the height of the bed to the lowest position after completing trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
0
16
2
2
Order By: Relevance
“…The aforementioned findings were not consistent with the findings of the study conducted by Tzeng and Yin (2008c), which showed that the mean staff working-height measurement taken in the afternoon (1:30 p.m. to 2:30 p.m.) was the highest (mean = 25.90 inches), followed by the one taken in the evening (6:30 p.m. to 7:30 p.m.; mean = 25.38 inches) and the one taken in the morning (9:30 a.m. to 10:30 a.m.; mean = 25.35 inches). This inconsistency may be due to different research designs and different practice cultures in the study units between Tzeng and Yin's study (2008c) and the current study.…”
Section: Discussion Of the Findingscontrasting
confidence: 89%
“…The aforementioned findings were not consistent with the findings of the study conducted by Tzeng and Yin (2008c), which showed that the mean staff working-height measurement taken in the afternoon (1:30 p.m. to 2:30 p.m.) was the highest (mean = 25.90 inches), followed by the one taken in the evening (6:30 p.m. to 7:30 p.m.; mean = 25.38 inches) and the one taken in the morning (9:30 a.m. to 10:30 a.m.; mean = 25.35 inches). This inconsistency may be due to different research designs and different practice cultures in the study units between Tzeng and Yin's study (2008c) and the current study.…”
Section: Discussion Of the Findingscontrasting
confidence: 89%
“…Staff commonly directs patients as to how much assistance they require, however intrinsic patient factors such as cognitive impairment, inability to follow directions, confusion, and poor judgment may impede patient compliance with hospital staff recommendations. These factors have consistently been identified as significant risk factors for in patient falls [21][22][23][24][25][26]. However, various hospital fall prevention programs have been implemented in the last decades in hospitals which require predetermined awareness, education and training for all nurses working in direct contact with patients.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy in fall prevention is to keep beds in a low position. [45] The analysis of the guidance revealed that the content related to the measurement of bed height to fit the person was consistent. Likewise the same measurements are used in a research paper by Capezuti et al [46] The findings from our study found some consistency between the different guidance leaflets.…”
Section: Discussionmentioning
confidence: 93%
“…However no further guidance is given as to whether this included duvet covers or where the person should sit. Nevertheless, Tzeng et al [45] suggest the measurement should be from the floor to the ''middle of the bed''.…”
Section: Discussionmentioning
confidence: 99%